(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Tourism National into economics high income what brings promising field is one of the leading sectors of the world economy. Tourism It is also the main source of income for some countries that have made progress in this area. exactly tourism Counts Our country another a lot of fields such as tourism in the field too this is a country with great opportunities.